(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The main problem in this service is the lack of teacher ability to carry out and write Classroom Action Research (CAR). Therefore, the purpose of this service is to develop the teacher’s ability to carry out and write CAR through the AKU RESTUI Bimtek (I Say Then Record Then Write in Instruments). The method of solving or the method of Bimtek AKU RESTUI includes; 1) developing the AKU RESTUI Bimtek instrument; 2) carrying out the Technical Guidance I am RESTUI; and 3) Follow-up After the Technical Guidance AKU RESTUI. The result achieved in the AKU RESTUI Bimtek is the compilation of 7 (seven) CAR proposals in groups. Therefore, it was concluded that the ability of teachers to prepare CAR proposals after the AKU RESTUI Bimtek was assessed as having been successfully improved because of the 6 (six) assessment indicators, 4 were recorded to have improved, namely; 1) formulate the title of the CAR proposal; 2) develop the introduction; 3) apply the CAR method; and 4) compiling CAR instruments. Meanwhile, there are 2 (two) that are still weak, namely; developing a literature review and the use of reference sources is still limited.